2012
DOI: 10.1038/onc.2012.368
|View full text |Cite
|
Sign up to set email alerts
|

Direct effects of Bmi1 on p53 protein stability inactivates oncoprotein stress responses in embryonal cancer precursor cells at tumor initiation

Abstract: Embryonal cancer can arise from postnatally persistent embryonal remnant or rest cells, which are uniquely characterized by the absence of p53 mutations. Perinatal overexpression of the MycN oncoprotein in embryonal cancer precursor cells causes postnatal rests, and later tumor formation through unknown mechanisms. However, overexpression of Myc in adult tissues normally activates apoptosis and/or senescence signals as an organismal defense mechanism against cancer. Here, we show that perinatal neuroblastoma p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 41 publications
4
55
0
Order By: Relevance
“…In this study we also found that over-expression of miR-200c caused similar effects that inhibited proliferation. It was also reported that over-expression of BMI-1 could cause p53 suppression, which provided evidence for the existence of some positive feedbacks [47,48]. In our study, we up-regulated BMI-1 through down-expression of miR-200c and found the approximate phenomenon, increased proliferation.…”
Section: Discussionsupporting
confidence: 75%
“…In this study we also found that over-expression of miR-200c caused similar effects that inhibited proliferation. It was also reported that over-expression of BMI-1 could cause p53 suppression, which provided evidence for the existence of some positive feedbacks [47,48]. In our study, we up-regulated BMI-1 through down-expression of miR-200c and found the approximate phenomenon, increased proliferation.…”
Section: Discussionsupporting
confidence: 75%
“…Recent findings have established that AATF genome encoded miR-2909 not only requires nuclear RelA translocation for its expression but also this microRNA regulates gene expression through repression of KLF4 gene expression resulting in the up-regulation of SP1 gene expression [7,8]. At this stage, it is pertinent to note that: a) SP1 has been shown to induce genes coding for AATF, CCL5 and p53 [13][14][15]; b) p53 gene expression is also induced by CCL5 and AATF-dependent translocation of RelA to p53 gene promoter [6,16]; c) KLF4 has been shown to induce IL-17 gene expression [12] and p53 binds RelA to block its translocation either to nucleus or mitochondria [4]; d) KLF4 is known to repress Bmi-1 gene which is known to degrade the p53 protein [17,18]. The results reported here together with above-mentioned findings in the literature, led us to the mechanism which reveals as to how AATF RNome can regulate UCP2 gene in a cyclic fashion (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Neuroblastoma is uniformly p53 wild-type at diagnosis, and previous studies have shown that p53 repression is critical for MYCN driven tumor initiation (41, 42). Most recently, BMI-1 mediated repression of p53 has been shown to play a key role in this process in TH-MYCN transgenic murine neuroblastoma (43). There is increased expression of genes, which restrict neural crest differentiation and inhibit apoptosis (e.g.…”
Section: Discussionmentioning
confidence: 99%